Ultrasound-microwave assisted extraction of flavonoid compounds from Eucommia ulmoides leaves and an evaluation of their antioxidant and antibacterial activities - Wang, Xiang; Peng, Mi-Jun; Wang, Zhi-Hong; Yang, Qiu-Ling; Peng, Sheng (Archives of Biological Sciences, 2020)
Paper description: The aim of this study is to improve the yield of flavonoid active ingredients from E. ulmoides leaves by establishing a high-performance extraction method. Ultrasound-microwave-assisted extraction was studied and the operational parameters were optimized by the Plackett-Burman and Box-Behnken design methods. Compared to conventional extraction methods and those using cell wall disruption, ultrasound-microwave-assisted extraction exhibited significantly high efficiency. Moreover, the obtained flavonoid extract exhibited prominent antioxidant and antibacterial activities. Ultrasound-microwave assisted extraction is a rapid and safe novel extraction technology, highly suitable for application in food and medical industries. Abstract: Ultrasound/microwave assisted extraction (UMAE) of flavonoid compounds from Eucommia ulmoides leaves was studied and the extraction conditions were optimized by the Plackett-Burman design (PBD) method combined with the Box-Behnken design (BBD). The antioxidant and antibacterial activities of the flavonoid extract were investigated. The results show that the optimal conditions were an ethanol concentration of 41%, microwave power of 178 W and an ultrasound extraction time of 26 min. Under these conditions, the yield of the flavonoid compounds was 2.454%±0.230%, which was higher than that after direct solvent extraction, ultrasound extraction and microwave extraction. The results of in vitro antioxidant assays showed that the flavonoid extract had scavenging capacity for DPPH, ABTS and hydroxyl radicals, with corresponding IC50 values of 30.76 mg/L, 21.09 mg/L, 248.4 mg/L, respectively. In addition, this extract exhibited strong antibacterial activity on Escherichia coli, Staphylococcus aureus and Salmonella typhimurium. https://doi.org/10.2298/ABS191216015W Received: December 16, 2019; Revised: April 14, 2020; Accepted: April 14, 2020; Published online: April 21, 2020 How to cite this article: Wang X, Peng M, Wang Z, Yang Q, Peng S.Ultrasound-microwave assisted extraction of flavonoid compounds from Eucommia ulmoides leaves and an evaluation of their antioxidant and antibacterial activities. Arch Biol Sci. 2020;72(2):211-21.